IMPLEMENTATION OF PEER TUTORING METHOD IN PAI LEARNING PROCESS TO IMPROVE STUDENTS' LEARNING MOTIVATION AT STATE SENIOR HIGH SCHOOL 1 SETIA BAKTI - Sri Dewi Lestari (Journal of Quality Islamic Education Research, 2025)
The background of this study is that the use of learning media is the most influential component in the implementation of the learning process, in reality there are still many educators who carry out learning without the help of learning media including Islamic Religious Education teachers at elementary, junior high, and high school levels. Likewise at SMP Negeri 2 Simpang Kanan, Rokan Hilir Regency, Islamic Religious Education and Character Education subject teachers also use traditional media. In learning, the use of video media is still very minimal (PAI Subject Teacher, SMP Negeri 2 Simpang Kanan, Rokan Hilir Regency, 2024). Therefore, the researcher intends to find out the causes of the less than optimal use of video learning media. The purpose of this study was to find out how to use video media in learning Islamic Religious Education and Character Education subjects at SMP Negeri 2 Simpang Kanan, Rokan Hilir Regency. In addition, identifying the advantages and disadvantages of learning Islamic Religious Education and Character Education using video media. The research method used is a qualitative method with a descriptive analysis approach. This type of research is field research. Data collection was carried out through interviews, observations and documentation. Then the data analysis was done by condensing the data, presenting the data and drawing conclusions. This study involved the principal, teachers and several students of Class VI at SMP Negeri 2 Simpang Kanan Kab. Rokan Hilir.